Chemopreventive effect and lack of genotoxicity and mutagenicity of the exopolysaccharide botryosphaeran on human lymphocytes - Malini, M.; Camargo, M. S. [UNESP]; Hernandes, L. C.; Vargas-Rechia, C. G.; Varanda, E. A. [UNESP]; Barbosa, A. M.; Dekker, R. F. H.; Matsumoto, S. T.; Antunes, L. M. G.; Colus, I. M. S. (Elsevier B.V., 2016)
Carbohydrate biopolymers of fungal-origin are an important natural resource in the search for new bioagents with therapeutic and nutraceutical potential. In this study the mutagenic, genotoxic, antigenotoxic and antioxidant properties of the fungal exopolysaccharide botryosphaeran, a (1 -> 3)(1 -> 6)-beta-D-glucan, from Botryosphaeria rhodina MAMB-05, was evaluated. The mutagenicity was assessed at five concentrations in Salmonella typhimurium by the Ames test. Normal and tumor (Jurkat cells) human T lymphocyte cultures were used to evaluate the genotoxicity and antigenotoxicity (Comet assay) of botryosphaeran alone and in combination with the mutagen methyl methanesulfonate (MMS). The ability of botryosphaeran to reduce the production of reactive oxygen and nitrogen species (RONS) generated by hydrogen peroxide was assessed using the CM-H(2)DCFDA probe in lymphocyte cultures under different treatment times. None of the evaluated botryosphaeran concentrations were mutagenic in bacteria, nor induced genotoxicity in normal and tumor lymphocytes. Botryosphaeran protected lymphocyte DNA against damage caused by MMS under simultaneous treatment and post-treatment conditions. However, botryosphaeran was not able to reduce the RONS generated by H2O2. Besides the absence of genotoxicity, botryosphaeran exerted a protective effect on human lymphocytes against genotoxic damage caused by MMS. These results are important in the validation of botryosphaeran as a therapeutic agent targeting health promotion. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Ames test; Comet assay; (1 -> 3)(1 -> 6)-beta-D-glucan; Jurkat cells; Human T lymphocytes; Antigenotoxicity